Whiteness in America - McDermott, Monica, 1971- (Cambridge, UK : Polity, 2020)
'The invisible root of racial inequality'--
Includes bibliographical references (pages 124-144) and index.
Keywords: Whites -- Race identity -- United States; United States -- Race relations -- Social aspects; Race awareness -- United States; Equality -- United States